Alkaloids as alternative probes to characterize the relative hydrophobicity of aqueous biphasic systems - Pereira, Jorge F. B. (2017)
In order to overcome the lack of characterization on the relative hydrophobicity of aqueous biphasic systems (ABS), the partition of three alkaloids as alternative probes, was evaluated in a series of biocompatible ABS composed of cholinium-based salts or ionic liquids (ILs) and polyethylene glycol (PEG). The caffeine partitioning in ABS was firstly addressed to infer on the effect of the phase-forming components composition. In all systems, caffeine preferentially concentrates in the lower water content PEG-rich phase. Additionally, a linear dependence between the logarithmic function of the partition coefficients and the water content ratio was found. To confirm this linear dependency, the partition coefficients of caffeine, theobromine and theophylline were determined in other ABS formed by different cholinium-based salts/ILs. In most systems, it is shown that all alkaloids partition to the most hydrophobic phase. To support the experimental results, COSMO-RS (Conductor-like Screening Model for Real Solvents) was used to compute the screening charge distributions of both phaseforming components of ABS and alkaloids, the excess enthalpy of mixing and the activity coefficients at infinite dilution. It is here demonstrated that the partition trend of alkaloids can be used to address the relative hydrophobicity of the coexisting phases in polymer-salt/-IL ABS.